2015
DOI: 10.5430/jnep.v6n4p122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of point 6 acupressure on chemotherapy associated nausea and vomiting among adolescents with cancer

Abstract: Background: Despite the development of effective antiemetic drugs, nausea and vomiting continue to be the primaryside effects associated with the usage of chemotherapy among adolescent with cancer. The aim of this study was to examine the effect of using acupressure Point 6 (P6) on reducing nausea and vomiting in cancer adolescents undergoing chemotherapy. Methods: A quasi experimental study was conducted at pediatric inpatients and outpatient departments of Mansoura oncology center. 60 cancer adolescents rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…One study (Reindl et al, 2006) reported that more than 40% of children continued to use acupuncture after the study ended, suggesting that their experiences were positive. Children also believed finger acupressure to be moderately effective (Abusaad & Ali, 2016). Less positive experiences included feeling discomfort from stimulation devices, including tightness from the acupressure band (Jones et al, 2008), itching from the auricular acupuncture pad (Yeh et al, 2012), and pain from acupuncture needles (Gottschling et al, 2008; Reindl et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…One study (Reindl et al, 2006) reported that more than 40% of children continued to use acupuncture after the study ended, suggesting that their experiences were positive. Children also believed finger acupressure to be moderately effective (Abusaad & Ali, 2016). Less positive experiences included feeling discomfort from stimulation devices, including tightness from the acupressure band (Jones et al, 2008), itching from the auricular acupuncture pad (Yeh et al, 2012), and pain from acupuncture needles (Gottschling et al, 2008; Reindl et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors reported that acupressure technique stimulates target acupoints on the body and promotes blood circulation which eliminate chemotherapy induced nausea and vomiting (42,43) . Others stated that acupressure relieves muscle tension and promote blood circulation which has a significant role in the reduction of nausea and vomiting (44) . In his study supported the application of acupressure at Pericardium six (PC6) and he found a significant reduction in frequency, duration and severity of nausea and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors reported that males are more liable to affect with childhood leukemia than females. They have a higher overall incidence of leukemia compared to females with a ratio of 2:1 (44,47,48) . This was congruent with the findings of the current study where the majority of children were males in the three studied groups (table 1) more than half of children's ages in the three groups were ranging from 7 to 9 years Effect of point 6 acupressure on chemotherapy associated nausea and vomiting among adolescents with cancer It was revealed from the present study that more than half of children's ages in the three studied groups ranged from 7 to 9 years (table 1).…”
Section: Discussionmentioning
confidence: 99%
“…[38] Abusaad and Ali (2016) studied the effect of acupressure among 60 adolescents with leukemia who received chemotherapy in Egypt and found significant reduction of the frequency, duration and severity of nausea, vomiting and retching in comparison with control group. [39] Shen and Yang (2017) concluded that, acupressure significantly increased the mean meridian energy and effectively decreased the severity of nausea and vomiting in lung cancer patients undergoing chemotherapy and recommend that, clinical nurses should provide acupressure as an intervention to relieve nausea and vomiting in patients receiving chemotherapy. [40] Byju et al (2018) evaluated the effectiveness of acupressure on the experience of nausea and vomiting among patients receiving chemotherapy and concluded that, acupressure is an effective method for reducing nausea and vomiting among patients receiving chemotherapy.…”
Section: Discussionmentioning
confidence: 99%